1995
DOI: 10.1037/0022-006x.63.2.296
|View full text |Cite
|
Sign up to set email alerts
|

Matching treatment focus to patient social investment and support: 18-month follow-up results.

Abstract: Patients were randomly assigned to 1 of 3 treatments: brief broad-spectrum (BBS), extended relationship enhancement (ERE), or extended cognitive-behavioral (ECB). A hierarchical latent growth model was used to analyze the data of 188 patients (82%) followed for 18 months. ERE treatment was significantly more effective in increasing abstinence of patients entering treatment with a network unsupportive of abstinence or with a low level of investment in their network, whereas BBS treatment was more effective for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(39 citation statements)
references
References 20 publications
(30 reference statements)
1
36
0
Order By: Relevance
“…Analyses revealed that for both women and men, longer lengths of residency in OH were significantly related to decreased social support for alcohol/drug use. This finding is an important one given the impact that such support has been found to have on drinking behaviors (Longabaugh et al, , 1995(Longabaugh et al, , 1998. That this relationship was stronger for women than men suggests the possibility that the process of recovery and the impact of variables such as social support may differ for women and men.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Analyses revealed that for both women and men, longer lengths of residency in OH were significantly related to decreased social support for alcohol/drug use. This finding is an important one given the impact that such support has been found to have on drinking behaviors (Longabaugh et al, , 1995(Longabaugh et al, , 1998. That this relationship was stronger for women than men suggests the possibility that the process of recovery and the impact of variables such as social support may differ for women and men.…”
Section: Discussionmentioning
confidence: 77%
“…Research in the area of addiction and recovery similarly highlights the important impact of social support networks on both individuals' substance use and abstinence (e.g., see Beattie & Longabaugh, 1997;Humphreys, Mankowski, Moos, & Finney, 1999;Longabaugh, Beattie, Noel, Stout, & Malloy, 1993;Longabaugh, Wirtz, Beattie, Noel, & Stout, 1995;Longabaugh, Wirtz, Zweben, & Stout, 1998). With respect to recovery, this research has found that specific social support for abstinence (vs. general social support) is directly and positively related to maintaining abstinence (Longabaugh et al, , 1998Mohr, Averna, Kenny, & Del Boca, 2001;Rice, Longabaugh, & Stout, 1997) and that this effect is strongest when the individuals are highly invested in these supportive networks (Longabaugh et al, , 1998.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…These patients tend to be younger than the general population, which could make it possible to detect risky drinking practices in the early stages (Antti-Poika & Karaharju, 1988). In addition, an injury is believed to increase receptivity of patients toward alcohol counseling, thus providing a "teachable moment" in which the aversive experience naturally produces a period where the individual is contemplating behavior change (Longabaugh, Wirtz, Beattie, Noel, & Stout, 1995;Gentilello et al, 1999). However, it has also been suggested that the traumatic experience of the injury and the subsequent emergency department visit and/or hospitalization could themselves yield a decrease in drinking independent of any interventions (Bombardier, Dawn, & Kilmer, 1997;Bombardier & Rimmele, 1998).…”
Section: Introductionmentioning
confidence: 99%